Peran Guru terhadap Kejenuhan Belajar Siswa di SD Negeri 02 Sungai Raya - Utami, Resti Yulia; Afryaningsih, Yunika; Listiarini, Yuni (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the pedagogical practices of teachers at SD Negeri 02 Sungai Raya, particularly in the application of learning methods, approaches to students, and learning evaluation. This study uses a qualitative approach with a case study type, where data is obtained through interviews with teachers from grades I to VI. The results of the study indicate that teachers actively implement a variety of learning methods, including limited lectures, group discussions, demonstrations, role-playing, the use of audiovisual media, simple experiments, and project-based learning. This variety of methods plays an important role in increasing students' interest, active participation, and understanding of concaepts, as well as accommodating different learning styles. In their approach to students, teachers apply humanistic and communicative strategies through emotional closeness, understanding individual circumstances, creating a comfortable learning environment, providing continuous motivation, special treatment, collaboration with parents, and instilling discipline. Meanwhile, evaluation is conducted at the end of the learning process using various methods, such as oral questioning, short assignments, quizzes, and written tests, which are tailored to the characteristics of the students and the material. Evaluation serves not only as a measure of understanding, but also as a diagnostic tool, a motivator, a means of reflection for teachers, and a communication tool for providing constructive feedback.